Bioactive glass-elicited stem cell-derived extracellular vesicles regulate M2 macrophage polarization and angiogenesis to improve tendon regeneration and functional recovery. (March 2023) - Xu, Hongtao; Zhu, Yanlun; Hsiao, Allen Wei-Ting; Xu, Jiankun; Tong, Wenxue; Chang, Liang; Zhang, Xuerao; Chen, Yi-Fan; Li, Jie; Chen, Wei; Zhang, Yingze; Chan, Hon Fai; et al.
Abstract: Effective countermeasures for tendon injury remains unsatisfactory. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs)-based therapy via regulation of Mφ-mediated angiogenesis has emerged as a promising strategy for tissue regeneration. Still, approaches to tailor the functions of EVs to treat tendon injuries have been limited. We reported a novel strategy by applying MSC-EVs boosted with bioactive glasses (BG). BG-elicited EVs (EVB ) showed up-regulation of medicinal miRNAs, including miR-199b-3p and miR-125a-5p, which play a pivotal role in M2 Mφ-mediated angiogenesis. EVB accelerated angiogenesis via the reprogrammed anti-inflammatory M2 Mφs compared with naïve MSC-EVs (EVN ). In rodent Achilles tendon rupture model, EVB local administration activated anti-inflammatory responses via M2 polarization and led to a spatial correlation between M2 Mφs and newly formed blood vessels. Our results showed that EVB outperformed EVN in promoting tenogenesis and in reducing detrimental morphological changes without causing heterotopic ossification. Biomechanical test revealed that EVB significantly improved ultimate load, stiffness, and tensile modulus of the repaired tendon, along with a positive correlation between M2/M1 ratio and biomechanical properties. On the basis of the boosted nature to reprogram regenerative microenvironment, EVB holds considerable potential to be developed as a next-generation therapeutic modality for enhancing functional regeneration to achieve satisfying tendon regeneration.